BPBL (Blended-Problem Base Learning) on Extraction and Chromatography Materials Using Coffee Topics to Measure Its Effectiveness on Student Learning Outcomes and Soft Skills - Yismia Ikha Sari; Irma Kartika Kusumaningrum; Surjani Wonorahardjo (Pascasarjana Universitas Negeri Malang (UM), 2021)
Abstract: Research and development of the BPBL’s teaching materials (Blended-Problem Base Learning) aim to measure its effectiveness on students learning outcomes (in extraction and chromatography courses) and their soft skills. Based on the preliminary questionnaire regarding the need for the development of the BPBL’s teaching materials states that the students felt quite difficult to understand the concepts in extraction and chromatography so their learning outcomes does not meet the standards. Students also realize that improving their soft skills is important for personal development, social participation, and success in the work environment. BPBL’s teaching materials are a combination between blended learning and problem-based learning. Using coffee as daily content is used to give meaningful learning for students and aim them to easily understand the concept in extraction and chromatography courses. The effectiveness of BPBL’s teaching materials on learning outcomes of students with n-gain is 0,64 or 64% and the effectiveness on soft skill of students with n-gain is 0,31% or 31%, both are included in the medium effectiveness category. Abstrak: Penelitian dan pengembangan bahan ajar berbasis BPBL (Blended- Problem Base Learning) bertujuan untuk mengukur efektifitasnya terhadap hasil belajar (pada materi ekstraksi dan kromatografi) dan soft skill mahasiswa. Angket pendahuluan mengenai perlunya pengembangan bahan ajar berbasis BPBL menyatakan bahwa mahasiswa merasa cukup kesulitan untuk memahami konsep pada materi ekstraksi dan kromatografi sehingga nilai hasil belajar mereka kurang memenuhi standart nilai yang ditentukan. Mahasiswa pun menyadari pentingnya meningkatkan soft skill yang mereka miliki untuk perkembangan pribadi, partisipasi sosial dan kesuksesan di lingkungan kerja. Model BPBL merupakan gabungan dari model pembelajaran blended learning dengan problem base learning. Penggunaan topik kopi sebagai konten sehari hari dalam pembelajaraan bertujuan untuk memberikan pembelajaran yang bermakna terhadap mahasiswa dan memudahkan mahasiswa untuk memahami konsep dalam ekstraksi dan kromatografi. Keefektifan bahan ajar berbasis BPBL terhadap hasil belajar mahasiswa menggunakan n-gain adalah sebesar 0,64 atau 64%, sedangkan keefektifan bahan ajar berbasis BPBL terhadap soft skill mahasiswa menggunakan n-gain adalah sebesar 0,31 atau 31%. Keduanya termasuk dalam kategori keefektifan sedang.